A long wavelength fluorescent probe for biothiols and its application in cell imaging. Issue 37 (1st September 2016) - Li, Jiawei; Yin, Caixia; Zhang, Yongbin; Chao, Jianbin; Huo, Fangjun
Abstract : A long wavelength and turn-on fluorescent probe (1 ) containing the maleimide group as a reactive site was designed and synthesized. Abstract : A long wavelength and turn-on fluorescent probe (1 ) containing the maleimide group as a reactive site was designed and synthesized. A series of sensing studies showed that probe1 was highly selective and sensitive with fast responses towards bio-thiols over non-thiolated amino acids in DMSO : HEPES = 1 : 1 (v/v, pH 7.4) solution. Furthermore, the detection limit was as low as 0.015 μM. More importantly, the potential application of probe1 as a biosensor for thiols was demonstrated by employing it in fluorescence imaging of Cys in HepG2 cells.